COATING OF PLATHYMENIA RETICULATA BENTH SEEDS WITH DIFFERENT MATERIALS - Priscila Gonçalves Figueiredo de Sousa; Henrique Duarte Vieira (Revista Eletrônica Científica Ensino Interdisciplinar, 2020)
Plathymenia reticulata Benth, popularly known as "˜vinhático"™, is a tree species with potential for the production of high-quality timber that is used in luxury furniture and construction. Seed coating ensures an adequate stand, vigorous plants, delayed onset of epidemics, and increased yield. The present study was carried out to investigate different types of seed-coating materials and their effects on the physical and physiological characteristics of Plathymenia reticulata Benth and define the best coating material. The coatings were made with sand, silicate, limestone, sand + silicate, sand + limestone and uncoated seeds as a control. The experiment was set up as a completely randomized design with six treatments tested in four replicates with 50 seeds each. Sand + limestone coating reduced GSI and ESI but did not influence the seedling germination or emergence rates. The best material for coating Plathymenia reticulata Benth was the sand + limestone mixture.